Preparation and Characterization of White Carbon Black From Rice Husk (Journal of Environmental Science and Natural Resources, 2017)
Generally white carbon black in a form of silica is used instead of carbon black as reinforcing filler for rubber compounding. In the present research white carbon black was prepared from rice husks in cost effective method with direct incineration of acid leaching rice husk. The physico-chemical properties of rice husk and the product of white carbon black obtained from rice husk were investigated by Thermogravimetry, Particle size analyzer, Scanning electron microscope; Fourier transformed infrared radiation (FTIR), X-ray fluorescence and X-ray difractometry analyses. It was found that the decomposition of organic constituents of rice husk was revealed by Thermo gravimetric and carbon, hydrogen, nitrogen, sulpher (CHNS) analyses. The FTIR spectrum showed presence of Si-O-Si band with a strong peak at 1085 cm-1. The analysis of particle size and scanning electron microscope demonstrated that the produced white carbon black represent different size of 112 ?m to 0.01 ?m with very small nano-particle and amorphous structure. The amorphous structure of product was also confirmed by XRD pattern. The high pure product as 99.9% was confirmed by XRF analysis. These types of product have potential application as filler in rubber compounding.J. Environ. Sci. & Natural Resources, 9(2): 1-7 2016